Efficient and Easy Conversion of Human iPSCs into Functional Induced Microglia-like Cells - Lanfer, Jonas; Winner, Beate; Kaindl, Johanna; Krumm, Laura; Acera, Miguel Gonzalez; Neurath, Markus; Regensburger, Martin; Krach, Florian (International Journal of Molecular Sciences, 2022)
Current protocols converting human induced pluripotent stem cells (iPSCs) into induced microglia-like cells (iMGL) are either dependent on overexpression of transcription factors or require substantial experience in stem-cell technologies. Here, we developed an easy-to-use two-step protocol to convert iPSCs into functional iMGL via: (1) highly efficient differentiation of hematopoietic progenitor cells (HPCs) from iPSCs, and (2) optimized maturation of HPCs to iMGL. A sequential harvesting approach led to an increased HPC yield. The protocol implemented a freezing step, thus allowing HPC biobanking and flexible timing of differentiation into iMGL. Our iMGL responded adequately to the inflammatory stimuli LPS, and iMGL RNAseq analysis matched those of other frequently used protocols. Comparing three different coating modalities, we increased the iMGL yield by culturing on uncoated glass surfaces, thereby retaining differentiation efficiency and functional hallmarks of iMGL. In summary, we provide a high-quality, easy-to-use protocol, rendering generation and functional studies on iMGL an accessible lab resource.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell differentiation; immunology; microglia; neurology; pluripotent stem cells

Generation and characterization of an endogenously tagged SPG11-human iPSC line by CRISPR/Cas9 mediated knock-in - Winner, Beate; Krumm, Laura; Pozner, Tatyana; Kaindl, Johanna; Regensburger, Martin; Günther, Claudia; Turan, Sören; Asadollahi, Reza; Rauch, Anita (Stem Cell Research, 2021)
Pathogenic bi-allelic variants in the SPG11 gene result in rare motor neuron disorders such as Hereditary Spastic Paraplegia type 11, Charcot-Marie Tooth, and Juvenile Amyotrophic Lateral Sclerosis-5. The main challenge in SPG11-linked disease research is the lack of antibodies against SPG11 encoded spatacsin. Here, we describe the CRISPR/Cas9 mediated generation and validation of an endogenously tagged SPG11- human iPSC line that contains an HA tag at the C-terminus of SPG11. The line exhibits multi-lineage differentiation potential and holds promise for studying the role of spatacsin and for the elucidation of SPG11-associated pathogenesis. Resource Table.

Genetically Single Generation and characterization of an endogenously tagged SPG11-human iPSC line by CRISPR/Cas9 mediated knock-in - Krumm, Laura; Pozner, Tatyana; Kaindl, Johanna; Regensburger, Martin; Günther, Claudia; Turan, Sören; Asadollahi, Reza; Rauch, Anita; Winner, Beate (Stem Cell Research, 2021)
Pathogenic bi-allelic variants in the SPG11 gene result in rare motor neuron disorders such as Hereditary Spastic Paraplegia type 11, Charcot-Marie Tooth, and Juvenile Amyotrophic Lateral Sclerosis-5. The main challenge in SPG11-linked disease research is the lack of antibodies against SPG11 encoded spatacsin. Here, we describe the CRISPR/Cas9 mediated generation and validation of an endogenously tagged SPG11- human iPSC line that contains an HA tag at the C-terminus of SPG11. The line exhibits multi-lineage differentiation potential and holds promise for studying the role of spatacsin and for the elucidation of SPG11-associated pathogenesis.
CRIS-Team Scopus Importer:2021-09-10

Neuroinflammatory disease signatures in SPG11-related hereditary spastic paraplegia patients. - Krumm, Laura; Pozner, Tatyana; Zagha, Naime; Coras, Roland; Arnold, Philipp; Tsaktanis, Thanos; Scherpelz, Kathryn; Davis, Marie Y.; Kaindl, Johanna; Stolzer, Iris; Süß, Patrick; Khundadze, Mukhran; et al. (Acta Neuropathologica, 2024)
Biallelic loss of SPG11 function constitutes the most frequent cause of complicated autosomal recessive hereditary spastic paraplegia (HSP) with thin corpus callosum, resulting in progressive multisystem neurodegeneration. While the impact of neuroinflammation is an emerging and potentially treatable aspect in neurodegenerative diseases and leukodystrophies, the role of immune cells in SPG11-HSP patients is unknown. Here, we performed a comprehensive immunological characterization of SPG11-HSP, including examination of three human postmortem brain donations, immunophenotyping of patients' peripheral blood cells and patient-specific induced pluripotent stem cell-derived microglia-like cells (iMGL). We delineate a previously unknown role of innate immunity in SPG11-HSP. Neuropathological analysis of SPG11-HSP patient brain tissue revealed profound microgliosis in areas of neurodegeneration, downregulation of homeostatic microglial markers and cell-intrinsic accumulation of lipids and lipofuscin in IBA1+ cells. In a larger cohort of SPG11-HSP patients, the ratio of peripheral classical and intermediate monocytes was increased, along with increased serum levels of IL-6 that correlated with disease severity. Stimulation of patient-specific iMGLs with IFNγ led to increased phagocytic activity compared to control iMGL as well as increased upregulation and release of proinflammatory cytokines and chemokines, such as CXCL10. On a molecular basis, we identified increased STAT1 phosphorylation as mechanism connecting IFNγ-mediated immune hyperactivation and SPG11 loss of function. STAT1 expression was increased both in human postmortem brain tissue and in an Spg11-/- mouse model. Application of an STAT1 inhibitor decreased CXCL10 production in SPG11 iMGL and rescued their toxic effect on SPG11 neurons. Our data establish neuroinflammation as a novel disease mechanism in SPG11-HSP patients and constitute the first description of myeloid cell/ microglia activation in human SPG11-HSP. IFNγ/ STAT1-mediated neurotoxic effects of hyperreactive microglia upon SPG11 loss of function indicate that immunomodulation strategies may slow down disease progression.
EVALuna2:552646

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Plasma Neurofilaments: Potential Biomarkers of SPG11-Related Hereditary Spastic Paraplegia - Krumm, Laura; Winkler, Jürgen; Winner, Beate; Regensburger, Martin (Movement Disorders, 2024)
CRIS-Team Scopus Importer:2024-03-08

RNA splicing modulator for Huntington's disease treatment induces peripheral neuropathy - Krach, Florian; Börstler, Tom; Neubert, Sebastian; Krumm, Laura; Regensburger, Martin; Winkler, Jürgen; Winner, Beate (iScience, 2025)
RNA splicing modulators, a new class of small molecules with the potential to modify the protein expression levels, have quickly been translated into clinical trials. These compounds hold promise for treating neurodegenerative disorders, including branaplam for lowering huntingtin levels in Huntington's disease. However, the VIBRANT-HD trial was terminated due to the emergence of peripheral neuropathy. Here, we describe the complex mechanism whereby branaplam activates p53, induces nucleolar stress in human induced pluripotent stem cell (iPSC)-derived motor neurons (iPSC-MN), and thereby enhanced expression of the neurotoxic p53-target gene BBC3. On the cellular level, branaplam disrupts neurite integrity, reflected by elevated neurofilament light chain levels. These findings illustrate the complex pharmacology of RNA splicing modulators with a small therapeutic window between lowering huntingtin levels and the clinically relevant off-target effect of neuropathy. Comprehensive toxicological screening in human stem cell models can complement pre-clinical testing before advancing RNA-targeting drugs to clinical trials.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Biological sciences; Cell biology; Cellular neuroscience; Natural sciences; Neuroscience; Pharmacology